2013
DOI: 10.1371/journal.pone.0078612
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate-Mediated Inhibition of Tartrate-Resistant Acid Phosphatase and Suppression of Bone Resorption of Osteoclasts

Abstract: Inorganic polyphosphate (poly(P)) has recently been found to play an important role in bone formation. In this study, we found that tartrate-resistant acid phosphatase (TRAP), which is abundantly expressed in osteoclasts, has polyphosphatase activity that degrades poly(P) and yields Pi as well as shorter poly(P) chains. Since the TRAP protein that coprecipitated with anti-TRAP monoclonal antibodies exhibited both polyphosphatase and the original phosphatase activity, poly(P) degradation activity is dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 37 publications
0
39
0
Order By: Relevance
“…The LTXXG motif in the region between β1 and β2 is also conserved [71] . It is interesting to note that some acid phosphatases, like the tartrate-resistant or purple acid phosphatase ( S9B Figure ) have exopolyphosphatase activity [72] and further work will be needed to investigate whether the exopolyphosphatase activity detected in acidocalcisomes [73] is due to this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The LTXXG motif in the region between β1 and β2 is also conserved [71] . It is interesting to note that some acid phosphatases, like the tartrate-resistant or purple acid phosphatase ( S9B Figure ) have exopolyphosphatase activity [72] and further work will be needed to investigate whether the exopolyphosphatase activity detected in acidocalcisomes [73] is due to this enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the nudix hydrolase family (NUDTs), which have been reported to cleave InsPs, can also cleave polyPs (Lonetti et al, 2011). In addition, the human purple acid phosphatase ACP5 is able to cleave polyP, with a substrate preference for short-chain polyPs (Harada et al, 2013).…”
Section: Enzymes Metabolizing Inorganic Polyphosphatesmentioning
confidence: 99%
“…It has been shown that phosphorous containing nanostructured or biomimetic surface coatings, as well as so-called bioactive implants, may offer a direct chemical bonding between bone and implant with improved osseointegration [ 23 , 24 , 25 , 26 , 27 , 28 ]. However, polyphosphoric acid and polyphosphates are easily hydrolysed in the body and, thus, quickly removed from the implant surface.…”
Section: Introductionmentioning
confidence: 99%